2022
DOI: 10.1136/bmjopen-2022-062508
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in health-related quality of life trajectories following myocardial infarction: national longitudinal cohort study

Abstract: ObjectivesTo investigate sex-based differences in baseline values and longitudinal trajectories of health-related quality of life (HRQoL) in a large cohort of myocardial infarction (MI) survivors after adjusting for other important factors.DesignLongitudinal cohort study.SettingPopulation-based longitudinal study the Evaluation of the Methods and Management of Acute Coronary Events study linked with national cardiovascular registry. Data were collected from 77 hospitals in England between 1 November 2011 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This aligns with ndings from a similar study in England, which found that women had lower health-related quality of life (HRQoL) compared to men among a large cohort of MI survivors, both at baseline and during the 12-month follow-up. Another study utilizing EuroQOL ve dimensions (EQ-5D-3L) questionnaire reported that women had higher impairment levels in mobility, self-care, usual activities, pain/discomfort, and anxiety/depression at each time point [22]. Studies done in India and Ethiopia, also showed that females have been shown to experience lower QoL after MI compared to their male counterparts [23].…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with ndings from a similar study in England, which found that women had lower health-related quality of life (HRQoL) compared to men among a large cohort of MI survivors, both at baseline and during the 12-month follow-up. Another study utilizing EuroQOL ve dimensions (EQ-5D-3L) questionnaire reported that women had higher impairment levels in mobility, self-care, usual activities, pain/discomfort, and anxiety/depression at each time point [22]. Studies done in India and Ethiopia, also showed that females have been shown to experience lower QoL after MI compared to their male counterparts [23].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that the HRQoL of women is lower than that of men at baseline and 12-month follow-up in patients with myocardial infarction; these results were similar to those of our study. 37 Another study on patients with hypertension revealed that in a group with poor CV health, women had lower HRQoL than men. 38 This may serve as evidence to suggest that women may have lower HRQoL than men when their CV health is poor.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors may contribute to a lower QoL for women than for men including being older, greater difficulty for older women in receiving care due to absence of a spouse, and greater prevalence of health comorbidities [34][35][36]. The higher prevalence of anxiety/depression among women than among men in the ideal group may be a major factor contributing to a lower QoL among women compared with that found in men [37,38].…”
Section: Plos Onementioning
confidence: 99%